A rapid method for isolation of total nucleic acids from Aspergillus nidulans - T. Y.-K. Chow; E. Käfer (Fungal Genetics Reports, 1993)
With the development of molecular biology techniques and their application to the analysis of cellular events, the isolation of total nucleic acids in Aspergillus nidulans for Southern and Northern hybridization has become routine.